Denmark and UN peacekeeping: glorious past, dim future. Issue 5 (19th October 2016) - Jakobsen, Peter Viggo
ABSTRACT: Denmark became a staunch supporter of UN peacekeeping during the cold war because it simultaneously served its interests and values and this winning combination meant that it relatively quickly became internalized as part of Denmark's foreign policy identity. Denmark turned its back on UN peacekeeping when NATO took over from the UN in Bosnia in 1995. Since then Denmark has prioritized NATO- and US-led operations. The Danish shift was driven by the interest in supporting the Western great powers as well as an altruistic desire to improve United Nations Protection Force's (UNPROFOR) dismal humanitarian record in Bosnia. This belief was also generated by the positive lessons learned from Denmark's pioneering use of tanks in UNPROFOR. This tank deployment and subsequent participation in NATO and US-led missions created a new warrior identity. This identity and the Danish interest in maintaining a close relationship to NATO's great powers make a major Danish return to UN peacekeeping unlikely.